Navigating Personal, Social, and Environmental Obstacles to Healthy Lifestyle in Jordanian Adolescents - Rula A. Amr; Ahmed M. Al-Smadi; Nanda Alqutob; Rand T. Akasheh (The Scientific World Journal)
Conclusion: These barriers may contribute to increasing childhood obesity rates in Jordan. Future interventions should prioritize creating a supportive environment that respects cultural norms, emphasizing high-quality parks, nutrition and sports education, healthier food options, student motivation, and park visits. Community engagement is crucial for fostering healthier lifestyles among Jordanian youth.